Modeling and Simulation in Engineering, Economics and Management : International Conference, MS 2016, Teruel, Spain, July 4-5, 2016, Proceedings /: International Conference, MS 2016, Teruel, Spain, July 4-5, 2016, Proceedings. (2016) - Unknown
No abstract available